The Role of Technology-Enabled Teaching and Learning in Enhancing Student-Student Interaction in Secondary Schools in Kampala District - Kaahwa, Taddeo Yuda; Nansamba, Florence; Muweesi, Charles (East African Journal of Education Studies, 2023)
Classroom interaction is the backbone of quality, inclusive, equitable and life-long learning. It is an avenue through which meaningful and quality education is developed. This study examined the role of technology enabled teaching and learning in enhancing student-student interaction in secondary schools in Kampala District - Uganda. The study followed a purely-qualitative tripartite case study design. The study participants included 9 teachers and 54 students that were purposively sampled. Observations of classroom lessons, semi-structured interviews of teachers and Focus Group Discussions of students were the major data collection methods used. The study found out that Technology-enabled teaching and learning facilitated student-student interaction as technology develops students’ skills in research and learning which are key to student-student interactions. Technology shaped students’ presentations and discussion in the class through provision of relevant information on the topics of discussion which further made discussions enjoyable with everyone contributing due to the readily available information. The study recommend that many secondary schools should allow students carry their own devices to school to make their learning easy and enjoyable. More tools like the interactive digital boards, should be employed in the classroom for better quality interactions. Keywords: Technology Enabled, Teaching/Learning, Classroom, Interaction.
Article